RELATIONSHIP BETWEEN SOCIAL INTERACTION ABILITY AND WRITING SHORT STORY ABILITY - Anggun Citra Dini Dwi Puspitasari; Zetty Karyati; Retna Ningsih (Universitas Indraprasta PGRI, 2019)
Abstract: Writing is one of the skills that is difficult to master because in writing, a person must exert all his abilities. So even in writing short story, often a writer has difficulty in getting ideas, themes, or topics to be writing. Ideas, themes, or topics will be easily obtained if the writer has extensive experience, insight, and knowledge. Extensive experience, insight, and knowledge can be obtained from social interaction. Based on this fact, the researchers suspect the relationship between social interaction ability with writing short story ability. Researchers assume if the higher of students ability will be. Therefore, researchers conducted research to find out the relationship between social interaction ability to writing short story ability. The method used in this research is descriptive qualitative. From this research it is expected to know whether there is a relationship between social interaction ability with writing short story ability. After doing research, the results show that there is a relationship between social interaction ability with writing short story ability.Key words: Ability, Social Interaction, and Writing Short Story.